2016
DOI: 10.3390/su8080816
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Security and Ecosystem Services in Response to Land Use Change in the Coastal Area of Jiangsu, China

Abstract: Urbanization, and the resulting land use/cover change, is a primary cause of the degradation of coastal wetland ecosystems. Reclamation projects are seen as a way to strike a balance between socioeconomic development and maintenance of coastal ecosystems. Our aim was to understand the ecological changes to Jiangsu's coastal wetland resulting from land use change since 1977 by using remote sensing and spatial analyses. The results indicate that: (1) The area of artificial land use expanded while natural land us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 83 publications
0
50
0
Order By: Relevance
“…Coastal regions are exposed to a wide variety of hazards, such as landscape changes, habitat loss, seawater intrusion, coastal flooding and waterlogging, which are exacerbated by climate change [31,32,33]. Moreover, many marine and coastal projects have been developed to meet human needs [34,35], and the demand for such developments in coastal regions is often met by exploiting natural land (e.g., tidal flats, water, and open spaces), which may considerably reduce the area of ecological land [27]. Importantly, China’s growing economy is increasingly concentrated in coastal regions [36]; thus, the outline of the Jiangsu coastal reclamation development plan (2010–2020) was passed in 2009 [27], and landscapes such as tidal flats, and areas of cordgrass and open seawater are to be used for agriculture and urban development.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal regions are exposed to a wide variety of hazards, such as landscape changes, habitat loss, seawater intrusion, coastal flooding and waterlogging, which are exacerbated by climate change [31,32,33]. Moreover, many marine and coastal projects have been developed to meet human needs [34,35], and the demand for such developments in coastal regions is often met by exploiting natural land (e.g., tidal flats, water, and open spaces), which may considerably reduce the area of ecological land [27]. Importantly, China’s growing economy is increasingly concentrated in coastal regions [36]; thus, the outline of the Jiangsu coastal reclamation development plan (2010–2020) was passed in 2009 [27], and landscapes such as tidal flats, and areas of cordgrass and open seawater are to be used for agriculture and urban development.…”
Section: Introductionmentioning
confidence: 99%
“…The method is coarse and still requires further improvements in order to allow analysis of results with greater detail. Although some research indicates that the macrozoobenthos communities can benefit from lower-intensity changes [2], the coastal reclamation area will take more than 30 years to recover to its equilibrium [47,73]. The dynamic interactions between the land and ocean make ecosystems of the coastal wetlands more vulnerable than other regions.…”
Section: Discussionmentioning
confidence: 99%
“…Reclamation occurred around 1950 in the western part of the study area, and most of the marsh wetlands were reclaimed for aquiculture pond and cropland. Notably, the Outline of Jiangsu Coastal Reclamation Development Plan (2010-2020) was released by the State Council of China in 2009, which has greatly accelerated the pace of reclamation in the study area [47]. …”
Section: Study Areamentioning
confidence: 99%
“…To evaluate the ecological changes appropriate to Jiangsu's coastal wetland, Caiyao Xu et al analyzed ecological security and ecosystem services in the region by using remote sensing and spatial analyses for the period from 1977 to 2014 [4]. They found that the total ecosystem service value decreased significantly from $2.98 billion per year to $2.31 billion per year over the study period due to this transformation from open to built-up land.…”
Section: Governance Issues For the Sustainability Of Asiamentioning
confidence: 99%
“…Moreover, it will take 34 years for landscape ecological security and 39 years for ecosystem services to regain their original state of equilibrium. Nonetheless, food production was the only ecosystem service function that consistently increased, mainly because of government policy, implying that government regulation or incentives regarding the transformation and/or utilization of the land could be the best solution for green growth in the region [4].…”
Section: Governance Issues For the Sustainability Of Asiamentioning
confidence: 99%